Bodies, Sovereignties, and Desire: Aboriginal Women's Writing of Québec. (June 2015) - Henzi, Sarah
Abstract : This paper examines how the works of Quebec Aboriginal women writers and filmmakers explore different kinds of relationships – between men and women, elders and youth, oppressors, victims and lovers – and how individuals within a society are informed to function in a certain way based on the "normativity" of these interrelationships. More importantly, by providing a tribune that speaks beyond linguistic and generational divides, they address the disappearance (or erasure), through colonial practices, of intimacy and vulnerability, and how these need to be reinscribed into how we relate to and narrate one another. They are, to quote Cherokee scholar Daniel Heath Justice, teachings in "how to be a better relative" that explore the complexity of the process of textualizing or otherwise materializing storytelling traditions and concepts of kinship.